The organization of physical and therapeutic care for the patients at the dental appointment - Smіrnova, Іryna; Смірнова, Ірина Віталіївна (Запоріжжя: Асоціація сприяння глобалізації освіти та науки "СПЕЙСТАЙМ", 2019)
Relevance: In dentistry, more than 99% of patients are serviced on an outpatient basis, more than 90% of the population have caries and its complicated forms, and 40% have periodontal disease [4]. The need for treatment by a therapeutic dentist is increasing year by year with an increase in incidence.
Keywords: rehabilitation; stomatological care; physiotherapy; quality of medical care